Armed Architectures/Weapons of Architecture (diségno, 2021)
The need to ‘connect’ appears, today, stronger the more pervasively the tendency to ‘separate’ and build barriers manifests itself. And it is exactly those physical and/or virtual barriers, in a broad sense, which are the places where the conflict between peoples and cultures are manifested, the background of a narrative horizon that will be tentatively explored, renouncing first of all the consideration of architecture as a neutral protagonist of this story, but declaring, instead, right from the start, the impossibility of its ‘innocence’ (read more).